Homoeopathy for delayed onset muscle soreness: a randomised double blind placebo controlled trial. Issue 4 (December 1997) - Vickers, A J; Fisher, P; Smith, C; Wyllie, S E; Lewith, G T
Abstract : OBJECTIVE: To pilot a model for determining whether a homoeopathic medicine is superior to placebo for delayed onset muscle soreness (DOMS). DESIGN: Randomised double blind placebo controlled trial. SETTING: Physiotherapy department of a homoeopathic hospital. SUBJECTS: Sixty eight healthy volunteers (average age 30; 41% men) undertook a 10 minute period of bench stepping carrying a small weight and were randomised to a homoeopathic medicine or placebo. OUTCOME MEASURES: Mean muscle soreness in the five day period after the exercise test, symptom free days, maximum soreness score, days to no soreness, days on medication. RESULTS: The difference between group means was 0.17 in favour of placebo with 95% confidence intervals +/- 0.50. Similar results were found for other outcome measures. CONCLUSION: The study did not find benefit of the homoeopathic remedy in DOMS. Bench stepping may not be an appropriate model to evaluate the effects of a treatment on DOMS because of wide variation between subject soreness scores.